Strengthening Neurological and Familial Interventions: Adult Coping Following Pediatric Brain Injury and Comorbidity - Angela; Sangeeta Kakkar; Ritika Chauhan (International Journal of Emergency and Trauma Nursing and Practices, 2024)
Background: Pediatric traumatic brain injury (PTBI) contributes to long-term physical, cognitive, and emotional difficulties and is a major cause of mortality and disability in children. An estimated 200,000 fatalities in India each year are attributed to traumatic brain injuries, with PTBI accounting for a significant share of these cases. Accidents, abuse, and sports injuries are just a few of the causes of post-traumatic brain injury (PTBI), which can result in comorbid illnesses including melancholy, anxiety, and trauma that might not show symptoms until adulthood. Objective: With an emphasis on therapies that can enhance emotional regulation and enhance long-term results, the study intends to investigate the psychological effects of PTBI on both the afflicted people and their parents. Methods: A thorough overview of the body of research on PTBI, co-occurring mental illnesses, and family-centered therapies is included in the review. The efficiency of different strategies RCTs and other pertinent studies are used to evaluate methods like motivating tactics, and hypopituitarism therapy. Results: Research indicates that after post-traumatic brain injury (PTBI), organised family therapies greatly enhance parental emotional control, interpersonal skills, and child conduct. Better healing and psychological adjustment are facilitated by methods that emphasize cognitive rehabilitation and motivational techniques. Conclusion: Family-centered therapies are essential for treating PTBI's physiological and psychological effects. These treatments improve children's chances of recovery while also giving their families the vital emotional support they need, which promotes general well-being. Importance: The study highlights the need for targeted mental health interventions, such as connections with family members and cognitive rehabilitation, to address the complex challenges related to PTBI. Implementing these strategies could improve the long-term outcomes of impacted people and their families.
Keywords: Psychological-cum-physiological; and shaken baby syndrome; parental emotional management; pediatrics